2016
DOI: 10.1016/j.jbmt.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between women's consultations with a massage therapist and health-related quality of life? Analyses of 1800 women aged 56–61 years

Abstract: Background: The use of complementary and alternative medicine (CAM) is commonplace in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…The findings reported here indicate that women increase their use of massage therapy as their quality of life decreases. This finding is consistent with other studies reporting that women with significantly poorer physical and emotional heath and poorer quality of life were more likely to seek massage therapy for their back pain and joint pain [ 19 , 54 ]. A qualitative study reported participants experienced an improved quality of life associated with receiving massage therapy [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings reported here indicate that women increase their use of massage therapy as their quality of life decreases. This finding is consistent with other studies reporting that women with significantly poorer physical and emotional heath and poorer quality of life were more likely to seek massage therapy for their back pain and joint pain [ 19 , 54 ]. A qualitative study reported participants experienced an improved quality of life associated with receiving massage therapy [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study reporting on prevalence of massage use in young and mid-aged women found that 42% of young Australian women and 25% of mid-aged women consulted a massage therapist [ 13 ]. Another study reporting on the use of CM among 1800 Australian women aged 56-61 years, 51% consulted a massage therapist within the previous 12 months [ 19 ]. The contrast in findings here may be due to previous studies reporting on various set age ranges up to 61 years, where findings reported from this study included women 45 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation